The politics of development geographies: new partners, transdisciplinary perspectives. A conversation with Emma Mawdsley - Bachmann, Veit; Mageza-Barthel, Rirhandu; Mawdsley, Emma (ERDKUNDE, 2020)
This contribution centres around a conversation with Emma Mawdsley, held at Goethe-University Frankfurt on 31 January 2019 in the context of the closing events of the programme on ‘Africa’s Asian Options’ (AFRASO) – a large interdisciplinary research programme, funded by the German Ministry for Education and Research (BMBF) between 2013 and 2019. During this time, we investigated the heterogeneous spaces of interaction between Africa and Asia; it closed with a lecture series, entitled ‘Afrasian Futures’ during which Emma Mawdsley delivered the final lecture. In this contribution, we address contemporary debates and the evolution of development geography, focussing in particular on Mawdsley’s rich contributions as regards the role of ‘new’ development partners, such as China and so called ‘emerging economies’, and South-South cooperation as well as on transdisciplinary connections of the subdiscipline. It starts with an introductory part in form of a brief reflection on the role of development geography in the wider context of academic engagement with the broad complex of ‘development’, in particular as regards the interdisciplinary field of ‘development studies’. In the following we highlight two key aspects of Mawdsley’s work and contribution to such research: i) a long-term shift away from North-South towards South-South relations; and ii) an emphasis on socio-political dimensions of development geography through feminist and queer perspectives. Following an initial introduction, the remainder of the contribution consists of a conversation with Emma Mawdsley.